Black Chokeberry (Aronia melanocarpa) Functional Beverages Increase HDL-Cholesterol Levels in Aging Rats - Daskalova, Elena (Foods, 2021)
Plant-based foods rich in phenolic phytochemicals are among the promising strategies to counteract age-related changes in lipid profile. Aronia melanocarpa (AM) fruits are a rich source of phenolic compounds possessing lipid-modulating effects. The present study investigated the effect of 3-month supplementation of AM-based functional beverages on the lipid profile of healthy aging rats. Male Wistar rats (n = 40) were separated into five groups: (YC) young controls (2-month-old); (AC) adult controls (13-month-old); (A) adult animals supplemented with pure AM extract; (A + P) adult animals supplemented with pectin-enriched (1%) AM extract; (A + H) adult animals supplemented with AM extract enriched with a herbal mixture. Total cholesterol (TC), triglycerides (TG), HDL-cholesterol (HDL-C), LDL-cholesterol (LDL-C) and atherogenic indices were investigated at the end of the study. Adult controls demonstrated age-related dyslipidemia resulting in decreased HDL-C, and increased TG and TC/HDL index. The supplemented groups showed a significant increase in HDL-C levels: A + P (1.49 mmol/L) and A + H (1.61 mmol/L), respectively, vs. AC (1.09 mmol/L), p < 0.05. The TC/HDL-C and LDL-C/HDL-C indices were decreased in the A + P and A + H groups in comparison to the AC group (p < 0.05). These results indicate that supplementation with polyphenol-rich AM beverages can successfully alter HDL-C levels and this effect is further potentiated by pectin and herbs.